PELAKSANAAN PILKADA SERENTAK DI TENGAH PANDEMI COVID 19 (Jurnal Konstituen, 2020)
The Covid-19 pandemic has an impact on the obstruction of all life activities, one of which is the implementation of regional elections which was originally to be held simultaneously in September 2020 and then based on PERPPU Number 2 of 2020 has been postponed to December 2020. But until now there have been no signs that this pandemic will disappear. in the near future, because from day to day instead of decreasing, it is increasing. Then will the simultaneous regional elections be held on December 9 2020 in the midst of the Covid-19 pandemic? Or will the government further delay the simultaneous regional elections until the Covid-19 pandemic is declared gone?